Antioxidant Activity of Dechlorophyllation of Kejibeling Leaf (Strobilanthes crispu L.) Extract Using the Free Radical Reduction Method - Marda, Marda; Naid, Tadjuddin; Rahmawati, Rahmawati (Pharmaceutical Reports, 2024)
Kejibeling leaves (Strobilanthes crispus L.) from the Acanthaceae family is a medicinal plant that has medicinal properties. This research aims to determine and determine the antioxidant activity of the dechlorophyllation ethanol extract of kejibeling leaves (Strobilanthes crispus L.) based on the IC50 value with the DPPH method. Kejibeling leaf extract (Strobilanthes crispus L.) extracted by soxhletation method, wherein the extraction process uses two types of solvents of different polarity, to attract chlorophyll compounds and antioxidant compounds, the percent yield of chlorophyll extract is obtained 0.0352% and percent yield of dechlorophyllation ethanol extract 9.604%. Then tested the antioxidant activity using the DPPH method. The results showed that there was antioxidant activity with an IC50 value of 106.375 µg/mL, that is, the result shows moderate antioxidant activity, while quercetin as a comparison has very strong antioxidant activity with a value of 1.391 µg/mL.